Model Fishbein Dalam Menganalisis Preferensi Pembelian Sayuran Daun di Pasar Sentral Kabupaten Sinjai: Fishbein Model in Analyzing Leafy Vegetable Purchase Preferences at the Sinjai Regency Central Market - Nurlina, Agustina; Megawati, Megawati; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This research aims to analyze consumer preferences for purchasing leafy vegetables at the Central Market in North Sinjai District, Sinjai Regency. Consumer preferences (X) are measured based on the attributes of freshness, cleanliness, texture, and price. These variables serve as independent variables, while purchasing decisions (Y) serve as the dependent variable. The research method used is a quantitative descriptive approach using Fishbein analysis.The results show that overall consumer preferences have a preference score (Ao) of 20.63, indicating a positive consumer attitude toward leafy vegetables at the market. Individually, freshness has the highest preference score (21.11), followed by cleanliness (20.65), price (17.75), and texture (17.01). Thus, it can be concluded that freshness is the most dominant aspect influencing consumer preferences and purchasing decisions. This indicates that consumers at Sinjai Central Market prioritize the physical quality of the product, which can be seen and felt directly.